Value of botulinum toxin injections preceding a comprehensive rehabilitation period for children with spastic cerebral palsy: A cost-effectiveness study - Schasfoort, F; Dallmeijer, A; Pangalila, R; Catsman, C; Stam, H; Becher, J; Steyerberg, E; Polinder, S; Bussmann, J (Journal of rehabilitation medicine, 2018)
Despite the widespread use of botulinum toxin in ambulatory children with spastic cerebral palsy, its value prior to intensive physiotherapy with adjunctive casting/orthoses remains unclear. A pragmatically designed, multi-centre trial, comparing the effectiveness of botulinum toxin + intensive physiotherapy with intensive physiotherapy alone, including economic evaluation. Children with spastic cerebral palsy, age range 4-12 years, cerebral palsy-severity Gross Motor Function Classification System levels I-III, received either botulinum toxin type A + intensive physiotherapy or intensive physiotherapy alone and, if necessary, ankle-foot orthoses and/or casting. Primary outcomes were gross motor func-tion, physical activity levels, and health-related quality-of-life, assessed at baseline, 12 (primary end-point) and 24 weeks (follow-up). Economic outcomes included healthcare and patient costs. Intention-to-treat analyses were performed with linear mixed models. There were 65 participants (37 males), with a mean age of 7.3 years (standard deviation 2.3 years), equally distributed across Gross Motor Function Classification System levels. Forty-one children received botulinum toxin type A plus intensive physio-therapy and 24 received intensive physiotherapy treatment only. At primary end-point, one statistically significant difference was found in favour of intensive physiotherapy alone: objectively measured percentage of sedentary behaviour (-3.42, 95% confidence interval 0.20-6.64, p=0.038). Treatment costs were significantly higher for botulinum toxin type A plus intensive physiotherapy (8,963 vs 6,182 euro, p=0.001). No statistically significant differences were found between groups at follow-up. The addition of botulinum toxin type A to intensive physiotherapy did not improve the effectiveness of rehabilitation for ambulatory children with spastic cerebral palsy and was also not cost-effective. Thus botulinum toxin is not recommended for use in improving gross motor function, activity levels or health-related quality-of-life in this cerebral palsy age- and severity-subgroup.